New Approach for the Incidence of Ascites Syndrome in Broiler Chickens and Management Control the Metabolic Disorders - Hassanzadeh, Mohammad (International Journal of Poultry Science, 2008)
Metabolic diseases such as ascites in broiler chickens result in significant economic losses to the poultry industry. The syndrome is multifactorial and mainly caused by exogenous and/or endogenous factors. Occurrences among faster growing lines are even more pronounced under conditions that imposed an additional metabolic load on the birds such as low ambient temperature. So, particular interactions between the environmental as well as with the genetic factors, play an important role. The purpose of this paper is to review some of predisposing factors that increase ascites incidence and the preventive procedures that have emerge for reducing the incidence of metabolic disorders in broiler chickens. Additionally, spontaneous hypoglycaemia or spiking mortality syndrome is also briefly mentioned.